2000
DOI: 10.1006/viro.2000.0576
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibits Marek's Disease Virus Replication but Is Not the Single Decisive Factor in Interferon-γ-Mediated Viral Inhibition

Abstract: The purpose of this study was to determine to what extent nitric oxide (NO) may play a role in the antiviral-mediated effect of chicken IFN-gamma against the Marek's disease virus (MDV) RB-1B. NO-generating compounds S-nitroso-N-acetylpenicillamine (SNAP) and 3-morpholino-sydononimine (SIN-1) strongly inhibited RB-1B replication in chicken embryo fibroblasts (85%) in a dose-dependent manner. The addition of superoxide dismutase (SOD) did not alter the inhibitory effect of SIN-1, which is also known to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…For example, Djeraba and co-workers reported an increased IFN-γ mRNA expression in the splenocytes of vaccinated bird with CVI-988 strain and challenged with very virulent MDV, RB-1B strain (A Djeraba et al, 2000). In parallel, Abdulcareem et al, (2008) have reported an increased expression of IFN-γ gene in feather tips of CVI988 and HVT vaccinated chickens by 10 days PI (M F Abdul-Careem et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Djeraba and co-workers reported an increased IFN-γ mRNA expression in the splenocytes of vaccinated bird with CVI-988 strain and challenged with very virulent MDV, RB-1B strain (A Djeraba et al, 2000). In parallel, Abdulcareem et al, (2008) have reported an increased expression of IFN-γ gene in feather tips of CVI988 and HVT vaccinated chickens by 10 days PI (M F Abdul-Careem et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…IFN-γ has been reported to inhibit MDV replication by activating macrophages to initiate cell mediated cytotoxicity for MDV-infected cells (Lee, 1979;Djeraba et al, 2000;Djeraba et al, 2002). Furthermore, IFN-γ directly activates CD8+ CTLs to kill the virally-infected cells (Whitmire et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ expression is inversely proportional to IL-10 production, as IL-10 inhibits IFN-γ production in chickens (Rothwell et al, 2004). So it is logically to found lower expression of IFN-γ and progressive lymphoma formation due to MDV, as the main function of IFN-γ as antiviral activity (Djeraba et al, 2000;Lee, 1979;Xing and Schat, 2000a) was inhibited by over production of IL-10 produced by regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…NO is also a potent antiviral agent, and several papers have suggested that NO might play an important role during virus infection (Djerabe et al, 2000;Xing & Schat, 2000;Koci et al, 2004). In contrast, several studies in mouse models demonstrated that overproduction of free radicals, such as NO, contributed to development of pneumonia during influenza virus infection and caused pulmonary damage (Akaike et al, 1996;Kačergius et al, 2006).…”
Section: Introductionmentioning
confidence: 99%